Culture as a hiring criterion: Systemic discrimination in a procedurally fair hiring process - Dominique Meurs; Patrick A. Puhani (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2021)
Criteria used in hiring workers often do not reflect the skills required on the job. By comparing trainee performance for newly hired workers conditional on competitive civil service examination scores for hiring French public sector workers, we test whether women and men with the same civil service examination score exhibit similar performance in a job-related trainee programme. Both the civil service examination and trainee scores contain anonymous and non-anonymous components that we observe separately. We find that by the end of the trainee programme (first year of employment), women are outperforming men on both anonymous written and non-anonymous oral evaluations, a finding that holds both conditionally and unconditionally for the civil service examination results. According to further analysis, however, it is the anonymously graded 'essay on common culture' civil service examination that, unlike the other CSE components, disadvantages women in this particular context.
Keywords: H83; J45; J71; M51; 330; recruitment; disparate impact; systemic discrimination; audit